Bible Didactics and Social Inequality? Critical Considerations on the Interconnection of Religious Education and Heterogeneous Settings - Winkler, Kathrin (Religions, 2022)
This paper deals with the question, to what extent, in the German context, have biblical didactic implications and systemic requirements in religious education led to social inequality in heterogeneous classrooms. Based on four different case studies in elementary, middle, and vocational schools, an empirical insight is provided that sheds exploratory and descriptive light on the construction of reality in the context of biblical learning. The analysis clearly shows that physical as well as socialization-related limitations, structural and systemic conditions in the German school system, and also strangeness and existential irrelevance, are obvious barriers that prevent students in heterogeneous settings from accessing biblical learning. In the synopsis, with theological-pedagogical implications as well as didactical challenges, it becomes clear how necessary difference-sensitive Bible didactics in the context of heterogeneity and social inequality is. Finally, based on the empirical evidence of the analyzed case studies and the theoretical framings, concrete expectations for biblical learning in religious education, in relation to heterogeneity and social inequality, are highlighted.